UPAYA MENINGKATKAN MOTIVASI KERJA GURU MELALUI SUPERVISI KEPALA SEKOLAH BERBASIS KOMUNIKASI DI SMAN 11 TEBO TAHUN AJARAN 2019/2020 - WITENTIRELI WITENTIRELI (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2022)
This psychological social need can be in the form of good communication between researchers and head teachers, teachers and principals as leaders of educational institutions. In an effort to help solve these problems, the researchers offer a form of administrative communication supervision. The results of the implementation of this administrative communication supervision are suspected to make the school situation more conducive, especially if it is supported by an adequate work environment. This research is a school action research conducted in 3 cycles. Each cycle goes through stages of planning, action, observation and reflection. The purpose of this study was to increase the work motivation of SMA Negeri 11 Tebo teachers through Administration-Based Principal Supervision in Semester I of the 2019/2020 Academic Year. The fact proves that Administration-Based Principal Supervision can increase teacher work motivation, because it is able to clarify the teacher's duties in carrying out school management which will always be developed by teachers in carrying out their professional duties. This can be proven based on research data from cycle I to cycle III: Cycle I The highest score is 124. The lowest score is 86. The average score is 107.6. Cycle II The highest score is 140. The lowest score is 106. The average score is 127.7. Cycle III Highest score 172. Lowest score 140. Average score 160.6. ABSTRAKKebutuhan sosial psikologis ini bisa berupa komunikasi yang baik antara peneliti dengan kepala guru, guru dengan kepala sekolah selaku pimpinan lembaga pendidikan. Sebagai upaya membantu memecahkan masalah tersebut, maka peneliti menawarkan suatu bentuk supervisi komunikasi administrasi. Hasil dari pelaksanaan supervisi komunikasi administrasi ini ditengarai menjadikan situasi sekolah menjadi lebih kondusif apalagi jika didukung adanya lingkungan kerja yang memadai. Penelitian ini merupakan penelitian tindakan sekolah yang dilaksanakan dalam 3 siklus. Tiap siklus melalui penatahapan perencanaan, tindakan, observasi dan refleksi. Tujuan penelitian ini adalah meningkatkan motivasi kerja guru SMA Negeri 11 Tebo melalui Supervisi Kepala Sekolah Berbasis Administrasi pada Semester I Tahun Pelajaran 2019/2020. Kenyataan membuktikan bahwa Supervisi Kepala Sekolah Berbasis Administrasi dapat meningkatkan motivasi kerja guru, karena mampu memperjelas tugas guru dalam melaksanakan manajemen sekolah yang akan selalu dikembangkan guru dalam melaksanakan tugas profesinya. Hal ini dapat dibuktikan berdasarkan data hasil penelitian dari siklus I sampai dengan siklus III: Siklus I Skor tertinggi 124. Skor terendah 86. Skor rata-rata 107,6. Siklus II Skor tertinggi 140. Skor terendah 106. Skor rata-rata 127,7. Siklus III Skor tertinggi 172. Skor terendah 140. Skor rata-rata 160,6.